Using Communication Theory / An Introduction to Planned Communication - Olson Jean T; Signitzer Benno; Windahl Sven (Sage Publications, 1992)
This broad-ranging textbook provides a clear and comprehensive introduction to using communication theory in real-life communication activities. Preface, Introduction, The Basics, Conceptual Tools, The Nature of Communication Planning, Not All Problems are Communication Problems, Categorization of Basic Strategies, Theoretical Approaches to Communication Planning, Multi-Step Flow Approaches, A Network Approach, Systems Theory Perspectives, Social Marketing Perspectives, Communication Campaigns: A Meeting Place for Different Approaches, The Elements of Mass Communication Theories, The Sender/ Communicator, The Message, The Medium, The Audience, Effects, Glossary, Bibliography, Index.